Antihyperlipidemic activity of Marchantia paleacea herb and Zingiber officinale var. Rubrum rhizome ethanol extracts in Triton X-100-induced mice - Purkon, Dicki Bakhtiar; Ningsih, Padmasari Diah Ayu Kumala; Pambudi, Fatimah Ayu Putri; Widyastiwi, Widyastiwi; Roseno, M.H.; Haerussana, Ayu Nala El Muna; Fadhlillah, Faizah Min; Trinovani, Elvi (Faculty of Pharmacy, Universitas Pancasila, 2024)
Non-communicable diseases cause 71% of deaths in the world, one of which is caused by dyslipidemia. Dyslipidemia has been established as a cause of various non-communicable diseases such as obesity and heart disease. This study aims to determine the antihyperlipidemic activity of the ethanol extract of the liverworts of Marchantia paleacea (EEMP) and the rhizome of Zingiber officinale var. rubrum (EEZOR) on male mice induced by Triton X-100. Grouping the number of test animals per group based on the Federer formula. Triton X-100 is used as an inducer of hyperlipidemic given intraperitoneally at a dose of 140 mg/kg body weight. Total cholesterol levels were measured by the colorimetric enzymatic method (CHOD-PAP) using a UV-Vis clinic photometer. Results from ethanol extract of the herb liverwort Marchantia paleacea (EEMP) and red ginger rhizomes Zingiber officinale var. Rubrum (EEZOR) can respectively reduce total hypercholesterol levels in male mice induced by Triton X-100 whose data were analyzed using the One-Way Anova test. The results of optimal dose of EEMP 200 mg/kg bw had the highest percentage of antihyperlipidemic activity and effectiveness (%) and also had a significant reduction in total cholesterol levels compared to the negative control group (p<0.05). While the results for the optimal dose of EEZOR 1000 mg/kg bw with the highest percentage of activity and effectiveness (%) and having a significant decrease compared to the negative control group (p <0.05). In conclusion, these findings suggest that both extracts have potential as natural antihyperlipidemic agents that can be further explored in the management of hyperlipidemic (dyslipidemic) and related non-communicable diseases.